Playing with Time, Space, and Narrative in Arturo Pérez Reverte’s The Flanders Panel (La table des Flandres) - Kliszcz, Aneta (Załącznik Kulturoznawczy, 2020)
The article discusses hypertextuality as a composition dominant of Arturo Pérez Reverte’s The Flanders Panel (La table des Flandes). To achieve this aim it focuses on the relation between the novel and Borges’s oeuvre, but also its relation to crime fiction as such (in considering its involvement with different types of crime story). Also addressed is the question of impact of introducing different timelines and spatial planes on the composition of the novel.